2019
DOI: 10.1007/s13205-019-2001-4
|View full text |Cite
|
Sign up to set email alerts
|

Multi-trait PGP rhizobacterial endophytes alleviate drought stress in a senescent genotype of sorghum [Sorghum bicolor (L.) Moench]

Abstract: Root-tissue colonizing bacteria demonstrated with multiple PGP traits from sorghum plants were identified as Ochrobactrum sp. EB-165, Microbacterium sp. EB-65, Enterobacter sp. EB-14 and Enterobacter cloacae strain EB-48 on the basis of 16S rRNA gene sequencing. Here, the in vivo experiments using ½-MS media and ½-MS media + 15% PEG 8000 (for inducing drought stress) indicated stress tolerance imparting ability of these rhizobacterial endophytes in a non-stay green and senescent genotype (R-16) of sorghum. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…This genus was also isolated and characterized in the desert of southern Tunisia, and the genus was proposed as a potential plant growth promoter under salinity and drought conditions [ 53 ]. Other authors [ 54 , 55 ] have suggested that PGP bacteria isolated from extreme environments can be used as inoculants under similar conditions from where they were isolated; thus, bacteria isolated from a cold desert may be used to counteract cold stress, while bacteria isolated from arid conditions can be used to reduce drought effects [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…This genus was also isolated and characterized in the desert of southern Tunisia, and the genus was proposed as a potential plant growth promoter under salinity and drought conditions [ 53 ]. Other authors [ 54 , 55 ] have suggested that PGP bacteria isolated from extreme environments can be used as inoculants under similar conditions from where they were isolated; thus, bacteria isolated from a cold desert may be used to counteract cold stress, while bacteria isolated from arid conditions can be used to reduce drought effects [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial root endophytes isolated from drought-stressed maize plants showed significant plant growth promotion activity owing to IAA production, siderophore production, synthesis of GA and cytokinin and ACC deaminase activity (Sandhya et al, 2017). In a study carried out by Govindasamy et al (2020), drought-stressed sorghum plants inoculated with the root endophytic bacteria Ochrobactrum sp., Microbacterium sp., Enterobacter sp. and Enterobacter cloacae showed an improved level of growth and osmotic adjustment.…”
Section: Endophytesmentioning
confidence: 99%
“…The accumulation of Pro in plants, especially in leaves, is an important physiological indicator of plant stress resistance. 19 Therefore, the determination of Pro content can be used as a physiological index for drought resistance breeding. A large amount of Pro was induced in leaves under drought stress (Figure 4).…”
Section: Effect Of Fa On Pro Content and Recmentioning
confidence: 99%